Developing an Android-Based Application for Early Detection and Interventiono f Developmental Problems - Mardiyanti, Mardiyanti; Yuanita, Ita; Sulaksono, Ageng; Handayani, Maulina; Evitasari, Noor (Indonesian Journal of Global Health Research, 2024)
Telenursing SDIDTK (Stimulation, Detection, Early Intervention of Growth and Development) aims to assist nurses and nursing students in assessing children's growth and development. Objective: This study develops and evaluates the SDIDTK telenursing application. Method: Using a Research and Development (R&D) method, an Android-based mobile application was created, the features include: early detection of growth disorders, developmental deviations, hearing and vision tests, and behavioral and emotional issues, including autism and ADHD. The application was evaluated through expert judgement by pediatric nursing experts and a user acceptance test using the Technology Acceptance Model (TAM) with 104 nursing students. Results: Expert evaluations confirmed the content's appropriateness. User acceptance showed high behavioral intention to use the app (mean score = 21.14, SD±3.095). Ease of use was rated highly (mean score = 26.39, SD±2.977), and the app's usefulness received a mean score of 27.07 (SD±2.585). Significant correlations were found between convenience, usefulness, and behavioral intention to use, with Spearman's rho values of 0.641 and 0.858, respectively. Positive attitudes towards app use correlated with a Spearman's rho value of 0.648 (P < 0.000). Conclusions: The SDIDTK telenursing application help students in enhancing clinical learning experiences.